Saberes etnoictiológicos de pescadores da região da Usina Jupiá: perspectivas para a educação ambiental crítica - Longo, Gabriela Rodrigues (2024)
The ecosystems surrounding the upper Paraná river basin have high aquatic biodiversity, however, a change in the configuration of the landscape and the aquatic environment has been noticed locally and in scientific research, with the consequent decrease in the original ichthyofauna. In this context, the general objective of this work was to identify the anthropic environmental changes occurring in the aquatic ecosystem and ichthyofauna of the Usina Jupiá region, located in the upper Paraná river basin, based on a relation of knowledge and methodologies that originate the environmental knowledge, subsidy for Critical Environmental Education proposals. Related to the perception of local fishermen, the research found its initial basis in a bibliographical review and a survey of underwater images of the local landscape, which present contributions to detailing the context of the area and its changes over time. We used different methodologies in the search for a discussion of knowledge that integrates the different needs of the environment, and of human and non-human communities. To this end, we construct environmental knowledge from different data sources, expressing the importance of the relationship between different knowledge for its conception. And, it is in the relationship and the dialogue that we also produced our data analysis, based on the analysis contribution of the historical-cultural approach, which performs discourse analysis and the construction of meanings, here based on the theory that establishes concepts of the Circle of Bakhtin. In this sense, the results were presented with the formation of three pieces of knowledge that, when related, formed a fourth piece of knowledge, the environmental knowledge. It was noticed that, based on the relationship between the three types of knowledge, we reached an environmental knowledge that denotes the importance of popular knowledge for the construction of a new rationality, which leads to public policies that are more comprehensive to the diversity and contradiction of our material reality, based on a scientific knowledge that observes scientific research data and photographs that contextualize changes in the local landscape. We therefore understand that the environmental knowledge was only achieved through the relationship of knowledges, and dialogue with different representatives of environmental and cultural diversity. Finally, we idealize a way in which environmental knowledge can be achieved, aiming to work with Critical Environmental Education. This mode was illustrated in the conception of the four types of knowledge that were described based on our methodologies, results, and discussions, but also based on a model that demonstrated the interaction of different types of knowledge to create a dialogical knowledge. With this model, we created a proposal for using environmental knowledge for Critical Environmental Education, based on the relationship between three types of knowledge.